Relation Between Perception of Control of COVID-19 Pandemic and Cyberchondria Levels in Individuals With Chronic Diseases - Bahçecioğlu Turan, Gülcan; Özer, Zülfünaz; Teke, Neslihan (AVES, 2021)
Objective: Perception that internet is a reliable source for information on COVID-19 could increase the search intensity for more information, consecutively increasing confusion and distress feelings, thereby could contribute to cyberchondira during pandemic. This study was done to investigate the relationship between perception of control of COVID-19 pandemic and cyberchondria levels in individuals with chronic diseases. Material and Methods: This descriptive and correlational study was done between December 1-30, 2020 by snowball sampling method. Data collection forms prepared by GoogleDocs program were sent online (e-mail, whatsapp) to individuals older than 18 who had chronic diseases, and they were asked to fill out and share the forms with other people. In the study, 267 individuals responding to the questionnaire were included. Data were collected by “Introductory Information Form,” “Perception of Control of COVID-19 Scale (PCo-COVID-19)” and “Cyberchondria Severity Scale (CSS-15).” Results: Mean age of the participants was 58.07 ± 18.31, 65.8% were female, 71.8% were married, 41.7% were literate, 27.4% were retired, 63.9% had balanced income and expenses and 28.9% had diabetes. CSS-15 mean score was found as 29.51 ± 7.14, compulsion subscale as 3.99 ± 2.03, distress subscale as 4.59 ± 2.33, excessiveness subscale as 5.46 ± 3.35, reassurance subscale as 5.52 ± 3.12 and mistrust of medical professional subscale mean score was found as 9.944.62. Mean score for PCo-COVID-19 was determined as 3.37 ± 0.70, for macro control subscale as 3.46 ± 0.92, for micro control subscale as 3.47 ± 0.78, and for controllability subscale as 3.17 ± 0.89. A significant and negative relation was found between PCo-COVID-19 and CCS-5 total and distress subscale. There was significant and negative relation between macro control and CCS-15 total and distress, excessiveness and reassurance subscales. Also there was a significant negative relation between micro control and CCS-15 total and distress subscale. Conclusion: Individuals participating in the study were found to have high COVID-19 control perception and low cyberchondria levels. As the perception of control of COVID-19 increases, cyberchondria levels decrease. © 2022 Archives of Health Science and Research. All rights reserved.
Kronik Hastalığı Olan Bireylerde COVID-19 Salgını Kontrol Algısı İle Siberkondri Düzeyleri Arasındaki İlişki
Keywords: Chronic disease; COVID-19; Cyberchondria; Perception of control